2008
DOI: 10.1016/j.virol.2008.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Walleye dermal sarcoma virus Orf B functions through receptor for activated C kinase (RACK1) and protein kinase C

Abstract: Walleye dermal sarcoma virus is a complex retrovirus that is associated with walleye dermal sarcomas that are seasonal in nature. Fall developing tumors contain low levels of spliced accessory gene transcripts A and B, suggesting a role for the encoded proteins, Orf A and Orf B, in oncogenesis. In explanted tumor cells the 35 kDa Orf B accessory protein is localized to the cell periphery in structures similar to focal adhesions and along actin stress fibers. Similar localization was observed in mammalian cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…Up to now, it has been reported that RACK1 can be hijacked by viruses to affect viral replication, such as Epstein-Barr virus (55), mumps virus (56), sarcoma virus (57), and hepatitis C virus (58). Consistent with these reports, in this study we also found that knockdown of RACK1 suppressed IBDV growth.…”
Section: Discussionsupporting
confidence: 91%
“…Up to now, it has been reported that RACK1 can be hijacked by viruses to affect viral replication, such as Epstein-Barr virus (55), mumps virus (56), sarcoma virus (57), and hepatitis C virus (58). Consistent with these reports, in this study we also found that knockdown of RACK1 suppressed IBDV growth.…”
Section: Discussionsupporting
confidence: 91%
“…These models suggest that wounding activates the MAPK pathway and initiates uncontrolled IEG expression and cell transformation. While walleye dermal sarcoma might occur in association with natural wound sites on fish, during tumor growth, WDSV produces another protein, Orf B, which is capable of persistent signal activation without external stimuli (5,7,95). It is localized in the cytoplasm and plasma membranes (7,8,95) and constitutively activates protein kinase C alpha (PKC␣) in NIH 3T3 cells (95).…”
Section: Discussionmentioning
confidence: 99%
“…PKC activation may contribute to cell survival and proliferation. RV-cyclin and Orf B probably cooperate to cause efficient tumor formation (Daniels et al 2008, Rovnak andQuackenbush 2010).…”
Section: Retroviruses Associated With Skin Tumors In Walleyesmentioning
confidence: 99%